2020
DOI: 10.1123/jpah.2019-0433
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of Parents’ Perceptions of the Neighborhood Environment and Children’s Physical Activity, Time Outside, and Screen Time

Abstract: Background: Increased physical inactivity and sedentary behavior among children are a global health concern. Purpose: Examine associations between parents’ perceived neighborhood environment and children’s physical activity, outside time, and screen time, and whether these associations were moderated by age and socioeconomic position (SEP). Methods: Parents (N = 1212) completed a survey during the Recording and EValuating Activity in a Modified Park study. The neighborhood perceptions (social and physical envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
0
21
1
Order By: Relevance
“…It is also plausible that other environmental and social variables were more salient determinants of students’ physical activity behavior in the present study than the psychological determinants identified in the current model. Research based on ecological determinants [ 76 , 77 ] and socio-structural predictors [ 78 , 79 ] of physical activity behavior illustrate the myriad of potential determinants of children’s leisure-time physical activity engagement, and a focus on psychological determinants alone may have neglected other potential predictors. As an example, students’ activity levels may have been influenced by environmental factors, such as access to sport clubs, ability to walk to school, and taking part in organized physical activity in their leisure time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also plausible that other environmental and social variables were more salient determinants of students’ physical activity behavior in the present study than the psychological determinants identified in the current model. Research based on ecological determinants [ 76 , 77 ] and socio-structural predictors [ 78 , 79 ] of physical activity behavior illustrate the myriad of potential determinants of children’s leisure-time physical activity engagement, and a focus on psychological determinants alone may have neglected other potential predictors. As an example, students’ activity levels may have been influenced by environmental factors, such as access to sport clubs, ability to walk to school, and taking part in organized physical activity in their leisure time.…”
Section: Discussionmentioning
confidence: 99%
“…As such, these factors may have been stronger determinants of physical activity than the current intervention, and were unlikely to change over the duration of the study. There is a need to augment models such as the TCM to include these ecological and socio-structural variables, which have proven to be important additional determinants of health behavior [ 76 , 79 , 80 ]. Indeed, overall, in developing interventions to a particular target group, it is useful to assess what needs and deficits there may be, and then select theory and match the intervention strategies according to this ‘needs assessment’ [ 81 ]; if levels of motivation and autonomy support already were high in this target group, perhaps the TCM was not the best suited theory to use as the (sole) basis of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…These studies represented a total of 188,498 unique participants and one study involving 422 Early Childhood Education and Care (ECEC) centers [70,105], with the analytic samples ranging between 100 and 29,159 and from 29 countries. Of 107 studies included, 27 studies were based on samples from the US [45, 46, 57, 62, 63, 66-69, 72, 77, 81-83, 87, 92, 93, 96, 102, 106, 118, 119, 121, 125, 126, 132], followed by Australia (n = 14) [31,36,50,51,53,54,65,105,114,116,122,[129][130][131] and Canada (n = 11) [50,60,61,73,76,98,105,115,117,135] (one study included both Australia and Canada [70]). There were 96 crosssectional [31-35, 38, 40-50, 52-56, 58-102, 104-110, 113-121, 123-130, 134-137] and 12 longitudinal studies (prospective, n = 11 [39,53,54,103,111,112,130,133,137]; retrospective, n = 1 [65]), of which two studies included both cross-sectional and longitudinal designs [37,96].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It is also plausible that other environmental and social variables were more salient determinants of students' physical activity behavior in the present study than the psychological determinants identi ed in the current model. Research based on ecological determinants [73,74] and socio-structural predictors [75,76] of physical activity behavior illustrate the myriad of potential determinants of children's leisure-time physical activity engagement, and a focus on psychological determinants alone may have neglected other potential predictors. As an example, students' activity levels may have been in uenced by environmental factors, such as access to sport clubs, ability to walk to school, and taking part in organized physical activity in their leisure time.…”
Section: Discussionmentioning
confidence: 99%
“…As such, these factors may have been stronger determinants of physical activity than the current intervention, and were unlikely to change over the duration of the study. There is a need to augment models such as the TCM to include these ecological and socio-structural variables, which have proven to be important additional determinants of health behavior [73,76,77]. Indeed, overall, in developing interventions to a particular target group, it is useful to assess what needs and de cits there may be, and then select theory and match the intervention strategies according to this 'needs assessment' [78]; if levels of motivation and autonomy support already were high in this target group, perhaps the TCM was not the best suited theory to use as the (sole) basis of the intervention.…”
Section: Discussionmentioning
confidence: 99%